TINJAUAN YURIDIS TERHADAP PUTUSAN PERCERAIAN ATAS NAFKAH ISTRI DAN ANAK DI PENGADILAN AGAMA LUBUK SIKAPING - S.Ag.,M.H., Habibulloh, (Menara Ilmu, 2017)
Divorce is the breakup of marriage, which can bring the result of a married coupleitself and to children born of these marriages, in accordance with the provisions of theCompilation of Islamic Law Article 114 until 115 that the breakdown of marriage due todivorce can occur because of divorce or based on a lawsuit of divorce and The divorce canonly be done in front of the trial of the Religious Courts. And by Act No. 1 of 1974 marriageArticle 41 (c) The court may oblige states to the former husband to provide cost of living or todetermine an obligation for the ex-wife, liabilities in the form of Mut'a, living on the waitingperiod (when she was not nusyus ) And livelihood maintenance (hadhanah).The purpose of this study to assess the implementation of the judgment of divorceon his wife and children living in Lubuk Sikaping Religious Court and to assess if the verdictdivorce settlement on a living wife and children are not implemented. The research issociological juridical research with case approach by interviewing and processing data fromsecondary law material.Based on the research results is understood that the provision of a living idda (forthe wife who does not nusyus), mut'ah and living childcare (hadhanah) in the case of divorceby 2015 has been implemented voluntarily by ex-husband (the applicant) on hearing of thedivorce pledge and in case of divorce The absence of execution by a religious court because ofthe absence of an execution request from a party who feels aggrieved. And it is better for theGovernment to make a special regulation regarding the procedure of implementing thepayment of mut'ah, iddah and hadhanah so that it can reduce the possibility of theimplementation of the verdict by the applicant.Keywords: Divorce, wife and child's living.